Donor derived HSV hepatitis in a kidney transplant recipient leading to liver fibrosis and portal hypertension. Issue 1 (4th December 2018) - Shaw, Brian I.; Nanavati, Aditya J.; Taylor, Vanessa; Miller, Rachel A.; Kappus, Matthew; Barbas, Andrew S.
Abstract: The unexpected transmission of donor‐derived infection through organ transplantation is a rare event with current donor screening practices. In this case report we describe a probable donor‐derived transmission of Herpes Simplex Virus (HSV)‐2 via deceased donor kidney transplantation resulting in HSV hepatitis in the recipient. This manifested as acute liver failure which resolved with appropriate anti‐viral therapy. Following recovery from the acute liver insult, the patient developed fibrotic liver morphology and portal hypertension, an unusual departure from the typical course.